Proceedings of the Twenty-Ninth SIGCSE Technical Symposium on Computer Science Education 1998
DOI: 10.1145/273133.274315
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual models and cognitive learning styles in teaching recursion

Abstract: An experimental-research design was implemented in an attempt to understand how different types of conceptual models and cognitive learning styles influence novice programmers when learning recursion. The results indicate that in teaching recursion to novice programmers:. concrete conceptual models are better than abstract , conceptual models, . novices with abstract learning styles perform ,better than those with concrete learning styles, . abstract learners do not necessarily benefit more from abstract conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 14 publications
1
39
0
1
Order By: Relevance
“…Similarly, Rasmussen and Davidson-Shivers, [31]; Bostrom, Olfman and Sein, [32] and Wu, Dale and Bethel [33] all have reported that convergers and assimilators individuals are successful in learning computers and programming. Ben-Ari [34] and Machanick [35] investigated the cognitive and social aspects of learning leading to a greater understanding of students" preferences and performance in computer science education Campbell and Johnstone [22] studied student"s learning style and their achievement in their first year programming class using Kolb model.…”
Section: Learning Style and Student Achievements In Programming Coursementioning
confidence: 90%
“…Similarly, Rasmussen and Davidson-Shivers, [31]; Bostrom, Olfman and Sein, [32] and Wu, Dale and Bethel [33] all have reported that convergers and assimilators individuals are successful in learning computers and programming. Ben-Ari [34] and Machanick [35] investigated the cognitive and social aspects of learning leading to a greater understanding of students" preferences and performance in computer science education Campbell and Johnstone [22] studied student"s learning style and their achievement in their first year programming class using Kolb model.…”
Section: Learning Style and Student Achievements In Programming Coursementioning
confidence: 90%
“…A conceptual model provides a singular representation for a concept, system or event, and must be complete, coherent and precise. For recursion, there are some conceptual models widely accepted and used for teaching recursion [19] [42]. The most abstract one is the inductive model, defined as a mathematical formula where the base case is directly identified.…”
Section: B Recursion Visualizationmentioning
confidence: 99%
“…There have been many papers on teaching recursion (for example, Wu et al [8]), but only a few have focused on structural recursion. Structural recursion is very common in functional programming languages.…”
Section: Related Workmentioning
confidence: 99%